The Role of Accounting Conservatism in the Equity Market: Evidence from Seasoned Equity Offerings - Kim, Yongtae; Li, Siqi; Pan, Carrie; Zuo, Luo (The Accounting Review, 2013)
ABSTRACT Using seasoned equity offerings (SEOs) from 1989 to 2008, we examine the role of accounting conservatism in the equity market. We find that issuers with a greater degree of conservatism experience fewer negative market reactions to SEO announcements. We further show that an important mechanism through which conservatism affects SEO announcement returns is by mitigating the negative impact of information asymmetry. Additional analyses suggest that our results are not driven by the effects of other forms of corporate governance. We also find evidence that conservative issuers continue to use conservative accounting after the equity offerings. Taken together, our findings are consistent with the argument that accounting conservatism reduces financing costs in SEOs. Data Availability: Data used in this study are available from public sources identified in the study.